Are shallow-water shrimps proxies for hydrothermal-vent shrimps to assess the impact of deep-sea mining? - Mestre, Nélia (2021)
Polymetallic seafloor massive sulphide deposits are potential targets for deep-sea mining, but high concentrations of metals (including copper - Cu) may be released during exploitation activities, potentially inducing harmful impact. To determine whether shallow-water shrimp are suitable ecotoxicological proxies for deep-sea hydrothermal vent shrimp the effects of waterborne Cu exposure (3 and 10 days at 0.4 and 4 μM concentrations) in Palaemon elegans, Palaemon serratus, and Palaemon varians were compared with Mirocaris fortunata. Accumulation of Cu and a set of biomarkers were analysed. Results show different responses among congeneric species indicating that it is not appropriate to use shallow-water shrimps as ecotoxicological proxies for deep-water shrimps. During the evolutionary history of these species they were likely subject to different chemical environments which may have induced different molecular/biochemical adaptations/tolerances. Results highlight the importance of analysing effects of deep-sea mining in situ and in local species to adequately assess ecotoxicological effects under natural environmental conditions.